Pencegahan COVID-19 melalui Cuci Tangan yang Benar - Kristiani Desimina Tauho; Firda Chamelia Panna; Olga Claudia Dos Santos; Presty Adventri; Windika Novtavia Manggopa; Fanisa Carolin; Ren Sisca Novia; Erlin Pirena; Reny Rosalia Ruuru; Threceya Rambu L.H. Analalo; Dian Angeline Luhukay (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Washing hands is one way to prevent the transmission of Covid-19 which can be used from childhood. Therefore, this community service is carried out to improve children's knowledge, attitudes and skills regarding proper hand washing. This community service was carried out in the form of health education with discussion and simulation methods to the children of the Anugerah Orphanage, Salatiga City on March 10, 2021. The evaluation was carried out by looking at changes of cognitive, affective and psychomotor aspects. We found that in the cognitive aspect, the participants were able to understand and apply washing hands properly, on the affective aspect, the participants valuing the importance of washing hands properly and on the psychomotor aspect, the participants were able to imitate correct hand washing. It is recommended that caregivers continue to observe children in applying proper hand washing to achieve a psychomotor naturalization level and experiencing level of attitude.